2014
DOI: 10.1177/1532673x14545210
|View full text |Cite
|
Sign up to set email alerts
|

Lobbying Regulations and Political Equality in the American States

Abstract: Laws that regulate the conduct of professional lobbyists in statehouses across the nation are one attempt to ensure that citizens' opinions receive more equal consideration when elected officials make policy decisions. Do states with stricter lobbying regulations actually display more egalitarian patterns of political representation? Using public opinion measures from the National Annenberg Election Surveys and data on state policies, this article first demonstrates that state policy decisions are consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“… 39 Achen 1978; Blais and Bodet 2006; Burden 2004; Ellis 2012; Flavin 2015; Gershtenson and Plane 2007; Giger, Rosset, and Bernauer 2012; Golder and Stramski 2010; Griffin and Flavin 2007; Griffin and Newman 2008; Jessee 2009.…”
mentioning
confidence: 99%
“… 39 Achen 1978; Blais and Bodet 2006; Burden 2004; Ellis 2012; Flavin 2015; Gershtenson and Plane 2007; Giger, Rosset, and Bernauer 2012; Golder and Stramski 2010; Griffin and Flavin 2007; Griffin and Newman 2008; Jessee 2009.…”
mentioning
confidence: 99%
“…Fourth, since this study was particularly interested in how differences in state postsecondary finance and policy environments, economic and demographic contexts, and political conditions influenced state postsecondary interest system densities, it was important to control for state policies/regulations that impacted postsecondary interest group densities. In that regard, lobbying/interest group regulations (stringency of state lobbying, registration, and reporting regulations) have been shown to impact state interest group ecologies (Flavin, 2015;Newmark, 2005;Ozymy, 2010;Strickland, 2014). It was likewise conceivable that such regulations may impact postsecondary interest group densities, and therefore this study controlled for this possibility.…”
Section: Political Systemmentioning
confidence: 99%
“…Additional political considerations that do not fall easily within the ESA framework have also been tested. Among these include state political ideology and legislative professionalism (Berkman, 2001;Boehmke, 2002Boehmke, , 2008Gray et al, 2015;Kattelman, 2015) and whether lobbying regulations impact interest group ecologies (Flavin, 2015;Newmark, 2005;Ozymy, 2010;Strickland, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Page, concluded that “our analyses suggest that majorities of the American public actually have little influence over the policies our government adopts” (Gilens and Page, 2014). In another example, Patrick Flavin of Baylor University asked “Do states with stricter lobbying regulations actually display more egalitarian patterns of political representation?” His answer is yes (Flavin, 2015). …”
Section: Six Likely Pathogenic Mechanisms Responsible For the Dysfmentioning
confidence: 99%